Characterization of biocompatible NiCo2O4 nanoparticles for applications in hyperthermia and drug delivery - Kale, Sangeeta N.; Jadhav, Anil D.; Verma, Seema; Koppikar, Soumya J.; Kaul-Ghanekar, Ruchika; Dhole, Sanjay D.; Ogale, Satishchandra B. (Nanomedicine-Nanotechnology Biology and Medicine, 2012)
Monodispersed, superparamagnetic nickel cobaltite (NCO) nanoparticles were functionalized using mercaptopropionic acid (MPA). MPA conjugates with NCO forming a metal-carboxylate linkage, with the MPA-MPA interaction occurring via formation of disulfide bonds, leaving another carboxyl end free for additional conjugation. The cytotoxicity studies on NCO-MPA show cell viability of similar to 100% up to a dosage of 40 mu g/mL on SiHa, MCF7, and B16F10 cell lines, and on mouse primary fibroblasts. Time-dependent cell viability studies done for a duration of 72 hours showed the cell lines' viability up to 80% for dosages as high as 80 mu g/mL. Negligible leaching (<5 ppm) of ionic Co or Ni was noted into the delivery medium. Upon subjecting the NCO-MPA dispersion (0.1 mg/mL) to radiofrequency absorption, the nanoparticles were heated to 75 degrees C within 2 minutes, suggesting its promise as a magnetic hyperthermia agent. Furthermore, the amino acid lysine and the drug cephalexin were successfully adducted to the NCO system, suggesting its potential for drug delivery. From the Clinical Editor: NCO-MPA nanopartciles were found to be promising magnetic hyperthermia agents, suggesting potential future clinical applications. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cytotoxicity; drug delivery; Magnetic hyperthermia; Magnetic nanoparticles

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2014)
Co-sonication of curcumin and acidic sophorolipid in aqueous solution is shown to lead to a dramatic enhancement of curcumin bioavailability through size reduction and encapsulation. The interaction between the two is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, FE-SEM, TEM, Infrared spectroscopy and X-ray diffraction measurements. The cytotoxicity effects of curcumin on breast cancer cell lines, MCF-7 and MDA-MB-231, are shown to be significantly enhanced by the formation of its complex with sophorolipid. The relative cytotoxicity of curcumin with its SL(A) complex is more due to the presence of the glucose moiety. The results further suggest that sophorolipid based formulations, which solubilize and nano-encapsulate curcumin after lipid digestion, show great potential for curcumin cell entry.

Synthesis, characterization and in vitro study of biocompatible cinnamaldehyde functionalized magnetite nanoparticles (CPGF Nps) for hyperthermia and drug delivery applications in breast cancer - Wani, Kirtee D.; Kadu, Brijesh S.; Mansara, Prakash; Gupta, Preeti; Deore, Avinash V.; Chikate, Rajeev C.; Poddar, Pankaj; Dhole, Sanjay D.; Kaul-Ghanekar, Ruchika (Plos One, 2014)
Cinnamaldehyde, the bioactive component of the spice cinnamon, and its derivatives have been shown to possess anticancer activity against various cancer cell lines. However, its hydrophobic nature invites attention for efficient drug delivery systems that would enhance the bioavailability of cinnamaldehyde without affecting its bioactivity. Here, we report the synthesis of stable aqueous suspension of cinnamaldehyde tagged Fe3O4 nanoparticles capped with glycine and pluronic polymer (CPGF NPs) for their potential application in drug delivery and hyperthermia in breast cancer. The monodispersed superparamagnetic NPs had an average particulate size of similar to 20 nm. TGA data revealed the drug payload of similar to 18%. Compared to the free cinnamaldehyde, CPGF NPs reduced the viability of breast cancer cell lines, MCF7 and MDAMB231, at lower doses of cinnamaldehyde suggesting its increased bioavailability and in turn its therapeutic efficacy in the cells. Interestingly, the NPs were non-toxic to the non-cancerous HEK293 and MCF10A cell lines compared to the free cinnamaldehyde. The novelty of CPGF nanoparticulate system was that it could induce cytotoxicity in both ER/PRpositive/Her2 negative (MCF7) and ER/PRnegative/Her2 negative (MDAMB231) breast cancer cells, the latter being insensitive to most of the chemotherapeutic drugs. The NPs decreased the growth of the breast cancer cells in a dose-dependent manner and altered their migration through reduction in MMP-2 expression. CPGF NPs also decreased the expression of VEGF, an important oncomarker of tumor angiogenesis. They induced apoptosis in breast cancer cells through loss of mitochondrial membrane potential and activation of caspase-3. Interestingly, upon exposure to the radiofrequency waves, the NPs heated up to 41.6 degrees C within 1 min, suggesting their promise as a magnetic hyperthermia agent. All these findings indicate that CPGF NPs prove to be potential nano-chemotherapeutic agents in breast cancer.

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy (vol 4, pg 60334, 2014) - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2015)

Evaluating the anticancer activity and nanoparticulate nature of homeopathic preparations of Terminalia chebula - Wani, Kirtee; Shah, Nilesh; Prabhune, Asmita; Jadhav, Arun; Ranjekar, Prabhakar; Kaul-Ghanekar, Ruchika (Homeopathy, 2016)
Background: Breast cancer is the most common cancer diagnosed among women and is the second leading cause of cancer death. Homeopathic medicines are part of the alternative medicines that are given as a supportive therapy in breast cancer. The objective of this study was to investigate the anticancer activity of commercially available homeopathic preparations of Terminalia chebula (TC) and evaluate their nanoparticulate nature. Methods: Mother tincture (MT) and other homeopathic preparations (3X, 6C and 30C) of TC were tested for their effect on the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cell lines by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Cell growth assay was performed to analyze the effect of the different potencies on the growth kinetics of breast cancer cells. MT and 6C were evaluated for the presence of nanoparticles by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Results: MT decreased the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cells. However, the other potencies (3X, 6C and 30C) decreased the viability of only breast cancer cells without affecting the viability of the non-cancerous cells. All the potencies, MT, 3X, 6C and 30C, reduced growth kinetics of breast cancer cells, more specifically at 1:10 dilution at 24, 48 and 72 h. Under SEM, MT appeared as a mesh-like structure whereas under TEM, it showed presence of nanoclusters. On the other hand, 6C potency contained 20 nm sized nanoparticles. Conclusion: The current study reports the anticancer activity of homeopathic preparations of TC against breast cancer and reveals their nanoparticulate nature. These preliminary results warrant further mechanistic studies at both in vitro and in vivo levels to evaluate the potential of TC as nanomedicine in breast cancer.